Mutational analysis of the Tetrahymena telomerase RNA: identification of residues affecting telomerase activity in vitro. - Autexier, C (1998)
Telomere-specific repeat sequences are essential for chromosome end stability. Telomerase maintains telomere length by adding sequences de novo onto chromosome ends. The template domain of the telomerase RNA component dictates synthesis of species-specific telomeric repeats and other regions of the RNA have been suggested to be important for enzyme structure and/or catalysis. Using enzyme reconstituted in vitro with RNAs containing deletions or substitutions we identified nucleotides in the RNA component that are important for telomerase activity. Although many changes to conserved features in the RNA secondary structure did not abolish enzyme activity, levels of activity were often greatly reduced, suggesting that regions other than the template play a role in telomerase function. The template boundary was only altered by changes in stem II that affected the conserved region upstream of the template, not by changes in other regions, such as stems I, III and IV, consistent with a role of the conserved region in defining the 5' boundary of the template. Surprisingly, telomerase RNAs with substitutions or deletion of residues potentially abolishing the conserved pseudoknot structure had wild-type levels of telomerase activity. This suggests that this base pairing interaction may not be required for telomerase activity per se but may be conserved as a regulatory site for the enzyme in vivo.